Ethical Considerations in Oncology and Palliative Care Research During COVID-19. (May 2022) - Akard, Terrah Foster; Gilmer, Mary Jo; Hendricks-Ferguson, Verna L.
Background: Researchers and clinicians must collaborate to consider alternative approaches to conduct standard protocol activities and deliver interventions during the pandemic. The COVID-19 pandemic has required researchers at many institutions to modify traditional in-person research to virtually delivered activities and still adhere to healthcare ethical principles of beneficence, justice, and respect for persons. Our objective is to describe ethical considerations faced by nurse investigators who modified research conducted in pediatric oncology during the COVID-19 pandemic.Methods Review of research case examples.Results Two research study case examples are presented, including remote-participant recruitment via Facebook advertising and a virtually delivered web-based legacy intervention in a pediatric oncology randomized clinical trial. Challenges to modifying in-person approaches to remote strategies are also discussed, with examples of advantages and disadvantages presented from a study testing a human–animal interaction intervention for children with cancer.Discussion Our case information may assist other investigators in planning virtually delivered behavioral strategies for populations that may prefer the convenience of remote participation in research studies because of multiple family responsibilities in the care of a family member, during the pandemic and after. As researchers understand more about subjects' preferences to receive protocol activities (i.e., virtual vs. in-person delivery), they may be able to reduce risks of being unable to collect data because eligible subjects declined or withdrew from a study due to multiple-home responsibilities during the care of a family member with a serious or life-limiting condition.